(untitled) (Global Journal of Human-Social Science, 2023)
Staff motivation is one of the important components of small business management Modern challenges determine the need to clarify the factors of personnel motivation for the formation of effective motivation systems at small businesses which make up a significant amount in the economies of many countries The study of various forms of motivation used in various countries allowed the authors to form an algorithm for the development and implementation of a staff motivation system at small business enterprises of the Republic of Moldova which is currently a candidate for EU membership